Experimental flight test evaluation of the effects of rotor state measurements and feedback control on variable stability helicopters - Alexander, M. (My University, 2021)
The National Research Council of Canada Flight Research Laboratory (NRC-FRL) has been experimenting with high-order rotorcraft state measurements based on main rotor hub mounted sensor systems installed on the NRC Bell 412 Advanced Systems Research Aircraft (ASRA). Utilizing the NRC Bell 205A Airborne Simulator (AS), a model following flight test investigation of the effects of rotor state measurements and feedback on flying, handling and ride qualities was performed. Using an eight degree-of-freedom mathematical model of the Bell 412 ASRA that included rotor flapping dynamics, several control system designs were developed. Desktop simulation was used to investigate controllers designed using Root Locus Method (RLM), Classical Multivariable Control (CMC), and Eigenstructure Assignment Control (EAC) algorithms featuring rigid-body and rotor state dynamics and feedback. The research concluded that rotor state feedback of longitudinal and lateral disc tilt dynamics significantly improves inter-axis decoupling, disturbance rejection characteristics, rotor response dynamics, command tracking accuracy, and rigid-body bandwidth performance.